The impact of a residential fire on occupational engagement and performance: A reflexive narrative approach - Gregory Chown (Elsevier, 2024)
Residential fires are a devastating and stressful life event. The high number of residential fires per year and significant associated stressors impacts all aspects of daily life. This reflexive narrative approach highlights gaps in inpatient and outpatient burn care for those who have suffered a residential fire from an occupational therapy perspective. The findings show that healthcare professionals need to consider social support systems, use therapeutic listening, provide stress management techniques and be advocates throughout the recovery process.